TRAINING OF SCIENCE LITERACY SKILLS IN CHEMICAL EQUILIBRIUM THROUGH IMPLEMENTATION GUIDED INQUIRY LEARNING - Ragil Triyani; Utiya Azizah (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2020)
Science literacy is the main key to face challenges in the 21st century. The research aimed to describe the students’ science literacy on chemical equilibrium topic through implementation of guided inquiry learning model. The research design used is One-Group Pretest-Posttest Design. The research was conducted in class XI MIPA 4 of SMAN 3 Surabaya. Data obtained by instruments of multiple-choice tests of science literacy and observation sheet. The result showed that every aspect of students’ science literacy skills was increased in the medium criteria, it was indicated by an average gain score of 0.6 for competence to explain scientific phenomena and to evaluate data and design scientific investigations. Moreover competence of interpreting data and scientific evidence obtained gain score of 0.7. The result of this research indicated that the skill of science literacy had been trained to students.